Optimized Multiplex Probe Design Enables MERFISH-Based Spatial Transcriptomics Across Multiple Species - Tan Grahn,Hooi Min (2025)
Deciphering where genes are expressed within the complex architecture of cells and tissues requires advanced spatial transcriptomics techniques. This study focuses on Multiplexed Error-Robust Fluorescence In Situ Hybridization (MERFISH), a technique for spatial transcriptomic. The MERFISH experiment involves probes binding to specific RNA-targeted sequences within fixed cells and tissues. I developed a pipeline to design MERFISH probes applicable to multiple species using two probe design tools: PaintSHOP and the Oligo Designer Toolsuite (ODT). Furthermore, metagenomic data from healthy lung samples were analyzed to classify and estimate the abundance of microbial species, resulting in a comprehensive microbial list for probe design. This enabled the generation of MERFISH probes that can detect bacteria, which makes the pipeline especially valuable for lung microbiome studies. Cross-species homology screening was performed to ensure probe specificity across microbial, human, and mouse genomes. Additionally, all designed target, readout, and primer sequences were evaluated for secondary structure using minimum free energy (MFE) calculations. An initial codebook was generated, followed by further structural and thermodynamic analyses and hybridization efficiency screening to refine the final codebebook. This multi-species MERFISH probe design workflow supports high-specificity spatial transcriptomic studies and opens new avenues for investigating host–microbe–xenograft interactions.